Polis dalam dua zaman, sebelum dan selepas pembentukan Malaysia : Penglibatan Sarjan (B) Jeffri Mohd Asri - Abdul Rahman Mad Ali@Abang; Bilcher Bala; Ramli Dollah (2462-2095, 2020)
The task of defending the sovereignty of the country is not easy. Recognizing this fact, efforts to track down the warriors who serve the nation need to be worked out to honor and appreciate their struggle for future generations. The experience with the police force in two different periods, namely the British occupation, and Sabah's independence in Malaysia was a privilege for a police veteran named Sergeant (B) Jeffri Mohd Asi. He has received many medals for his invaluable service to the security forces, state of Sabah, and Malaysia in general. In the study of this paper, the methods used are library studies, archival studies and selected interviews among police veterans. In conclusion, this paper will reflect on his experiences and explain his involvement in important events before and after the establishment of Malaysia.